Variations in CCR5, but not HFE, ELMO1, or SLC12A3, are associated with susceptibility to kidney disease in north Indian individuals with type 2 diabetes CCR5变异而不是HFE、ELMO1或者SLC12A3变异与印度北部的2型糖尿病患者的肾病易感性相关 - Yadav, Ashok K.; Kumar, Vinod; Dutta, Pinaki; Bhansali, Anil; Jha, Vivekanand (Journal of diabetes, 2014)
Background Diabetic nephropathy (DN), the leading cause of end‐stage renal disease worldwide, may have a genetic component. In the present study, we investigated variations in a set of genes with susceptibility to DN in a north Indian population. Methods Four genes (HFE, ELMO1, SLC12A3, and CCR5) were selected on the basis of reported association with type 2 diabetes and nephropathy. In all, 417 diabetic subjects (215 without kidney disease [DM] and 202 with DN) and 197 healthy controls (HC) were evaluated for variations in HFE (845 G>A and 187G>C), SLC12A3 (g.34372G>A), CCR5 (59029A>G), and ELMO1 (+9170 G>A). Polymorphism analysis was performed by polymerase chain reaction–restriction fragment length polymorphism and Taqman allele discrimination assays. Results Significant differences were found in genotype and allelic frequency in SLC12A3 (g.34372G>A) between diabetic subjects and HC (P < 0.03). There were no differences in the SLC12A3 g.34372G>A (AA+GA) genotype between diabetic subjects with and without nephropathy. However, the CCR5 59029AA genotype and A allele were significantly more frequent in diabetics compared with the HC (P = 0.01 and 0.03, respectively) and subjects with DN versus DM (P = 0.002 and 0.01, respectively). For ELMO1 (+9170 G>A), the GG genotype frequency was higher in the diabetic versus HC group. There were no differences in the frequency of HFE‐845 G>A and HFE‐187G>C among the groups. Conclusion This study shows that the CCR5 AA genotype is over‐represented in subjects with kidney disease due to type 2 diabetes. The CCR5 59029G>A and ELMO1 (+9170 G>A) loci are more frequent, and the SLC12A3 34372 AA genotype is associated with a reduced risk of diabetes. 摘要 背景：在全世界范围内糖尿病肾病（Diabetic nephropathy，DN）都是导致终末期肾病的主要原因，其中可能包含有遗传成分的影响。在当前的这项研究中，我们在北印度人群中调查了一组DN易感基因的变异情况。 方法：在既往已经报告的与2型糖尿病以及肾病有关基因中挑选了4个基因（HFE，ELMO1，SLC12A3与CCR5）。总共入组了417名糖尿病受试者（其中215名没有糖尿病肾病[DM]，202名有DN）与197名健康对照者（HC），评估他们的HFE（845G>A与187G>C）、SLC12A3（(g.34372G>A）、CCR5（59029A>G）以及ELMO1（+9170 G>A）基因是否出现变异。使用聚合酶链反应限制性片段长度多态性分析法以及Taqman等位基因鉴别法进行多态性分析。 结果：发现SLC12A3（g.34372G>A）的基因型与等位基因频率在糖尿病受试者与HC之间具有显著差异（P < 0.03）。SLC12A3 g.34372G>A（AA+GA）基因型在合并与未合并肾病的糖尿病受试者之间没有差异。然而，无论是糖尿病受试者与HC相比（分别P = 0.01，P = 0.03），还是合并DN的受试者与DM组相比（分别P = 0.002，P = 0.01），前者出现CCR5 59029AA基因型与A等位基因的频率都明显更高。对于ELMO1（+9170 G>A）来说，与HC组相比较，糖尿病组出现GG基因型的频率更高。各组之间出现HFE‐845 G>A与HFE‐187G>C的频率没有差异。 结论：这项研究结果显示，由于2型糖尿病导致的肾病患者出现CCR5 AA基因型的频率更高。出现CCR5 59029G>A与ELMO1（+9170 G>A）基因型的频率更高，并且SLC12A3 34372 AA基因型与糖尿病风险的下降有关。